(untitled) (CIPEEX, 2024)
THE INSTITUTIONS THAT ENCOMPASS THE HEALTH AREA ARE FACED WITH SOME OBSTACLES TO BE FACED. IN THIS WAY, THE APPLICABILITY OF QUALITY MANAGEMENT TOOLS IN THESE ORGANIZATIONS IS OF FUNDAMENTAL IMPORTANCE IN THE SEARCH FOR CONTINUOUS IMPROVEMENT OF THE SERVICES OFFERED, IN THE PROMOTION OF PATIENT SAFETY AND ALSO IN THE OPTIMIZATION OF AVAILABLE RESOURCES. FROM THIS, THE PROPOSED OBJECT0069VO WAS TO REPORT ORIGINAL STUDIES THAT DISCUSS THE BENEFITS OF THE INSERTION AND DEVELOPMENT OF THESE QUALITY TOOLS WITHIN THE HEALTH SCOPE. THIS IS AN INTEGRATIVE REVIEW, IN WHICH THE ELECTRONIC SEARCH FOR PUBLIC ARTICLES TOOK PLACE IN ELECTRONIC DATABASES OF THE VHL (VIRTUAL LIBRARY IN HEALTH), GOOGLE SCHOLAR AND THE PORTAL OF CAPES JOURNALS, IN THE PERIOD FROM 2020 TO 2023, TOOLS OF QUALITY, HOSPITAL MANAGEMENT, HEALTH AND QUALITY ORGANIZATIONS. FROM THIS, THROUGH THE APPLICATION OF TOOLS SUCH AS THE PDCA CYCLE (PLAN-DO-CHECK-ACT), ISHIKAWA DIAGRAM, FLOWCHART AND CHECK SHEET, IT WAS ALLOWED THE IDENTIFICATION OF AREAS OF OPPORTUNITY AS WELL AS INEFFICIENCIES IN PROCESSES, IN ORDER TO ENABLE THE IMPLEMENTATION OF CORRECTIVE MEASURES THAT HELP REDUCE HOSPITAL INFECTIONS AND IMPROVE OVERALL PATIENT SAFETY. DESPITE THE DIFFICULTIES FACED WITH THE PROPAGATION OF CULTURE IN THE ORGANIZATIONAL CONTEXT, THE COMMITMENT TO THE APPLICABILITY AND CONTINUITY OF THE USE OF QUALITY TOOLS OF THE ENTIRE HIERARCHICAL LEVEL IS CRUCIAL TO ACHIEVE THE OBJECTIVES AND GOALS PROPOSED WITHIN THE INSTITUTION. THIS INVOLVES TRAINING EMPLOYEES TO IDENTIFY PROBLEMS, PROPOSE SOLUTIONS AND CONSTANTLY MONITOR RESULTS, IN ORDER TO PROMOTE A CULTURE OF CONTINUOUS IMPROVEMENT IN HEALTH ORGANIZATIONS, AS IT WILL CONTRIBUTE TO EXCELLENCE IN PATIENT CARE. ALSO, IT ENABLES OPERATIONAL EFFICIENCY, THE REDUCTION OF UNNECESSARY COSTS, ALLOWS THE MOST EFFECTIVE ALLOCATION OF RESOURCES AND ALSO PROPITIOUS THE STANDARDIZATION OF THE ACTIVITIES DEVELOPED, ENSURING THAT PROCEDURES ARE PERFORMED CONSISTENTLY AND IN ACCORDANCE WITH BEST PRACTICES, CONSIDERING THAT IN HEALTHCARE STANDARDIZATION CAN SAVE LIVES AND REDUCE MEDICAL ERRORS. THEREFORE, IT CAN BE INFERRED THAT THE APPLICABILITY OF QUALITY MANAGEMENT TOOLS IN HEALTH ORGANIZATIONS IS ESSENTIAL TO IMPROVE THE QUALITY OF SERVICES, OPTIMIZE RESOURCES, PROMOTE A CULTURE OF CONTINUOUS IMPROVEMENT AND ENSURE PATIENT SAFETY AND SATISFACTION, SINCE IT CAUSES THE REDUCTION OF SERVICE TIME AND QUEUES. AS HEALTH CHALLENGES CONTINUE TO GROW, EFFECTIVE USE OF THESE TOOLS BECOMES INCREASINGLY CRUCIAL TO THE SUCCESS OF ORGANIZATIONS AND THE WELL-BEING OF PATIENTS.